“MENINO JÁ NASCE MENINO, MENINA JÁ NASCE MENINA”: Fobia religiosa de gênero e suas implicações no debate sobre o Plano Nacional de Educação brasileiro no período 2012-2014 - COELHO, Fernanda Marina Feitosa (2017)
This dissertation deals with the gender-based phobia derived from the political-religious discourse of the "gender ideology" that creates obstacles to the sexual and reproductive rights of so-called minorities (both women and LGBT people), more specifically in the case of the National Education Plan (PLC no. 103/2012) approved by Law 13.005 on June 25, 2014, deprived of the gender guideline. Thus, the dynamics between the religious discourse and the exclusion of the gender guideline of the NEP 2014-2024 are verified. The main objective of the research is to characterize and explain the socioreligious production of moral panics (COHEN, 2002) related to gender through the formation of the knowledge of "gender ideology" and to concatenate speeches made by politicians of the Evangelical Parliamentary Front and of political religious leaders who evoked this knowledge also built by religion and use arguments that influenced the consolidation of said Plan sanctioned in 2014 without the gender guideline, initially included among its goals. Through bibliographical and documentary research, the theme of gender is presented as central to human rights and to human development itself and, therefore, the need for a gender education to deepen the increased awareness of respect for individuals. The political work of the evangelical group is analyzed in the NEP procedures as part of a resumption of conservatism that seeks to instrumentalize the state as the guardian of a predominantly Christian, patriarchal and heterosexist moral. The participation and religious influence in this processis, therefore, related and characterized as phobic with regard to the veto of the gender guideline, through the analysis of the content of the speeches that may denote the socioreligious production of gender-based phobia to corroborate with religious morality in the period.